Significados otorgados a la violencia simbólica experimentada por mujeres homosexuales de la localidad Antonio Nariño (2018)
This Degree Project seeks to analyze the meanings given to the symbolic violence experienced by homosexual women in the Antonio Nariño town of the city of Bogotá, since it is a type of violence that is constantly generated because societies Traditional practices have assigned a superior role to men with respect to the role of women, giving rise to constant inequalities in different scenarios, in which women with a different sexual preference are discriminated against and subject to various types of violence.